Evaluation of Bioplex Zn® as an Organic Zinc Source for Chicks - Ao, T.; Pierce, J.L.; Power, R.; Pescatore, A.J.; Cantor, A.H.; Ford, M.J. (International Journal of Poultry Science, 2006)
A study was conducted to evaluate Bioplex Zn® (a chelated Zn proteinate) as an organic zinc source for broiler chicks. Corn-soybean meal diet without Zn supplementation, containing 23 mg/kg Zn, was used as a basal diet. Day-old male broiler chicks were raised for three weeks. Feed and water with no detectable Zn (< 0.001 ppm) were supplied on an ad libitum basis. Treatments consisted of feeding the basal diet alone or with four supplemental levels of Zn (5, 10, 20 and 40 mg/kg) either from Bioplex Zn® or from analytical ZnSO4. 7H2O. Eight replicate cages of six chicks were randomly assigned to each of nine dietary treatments. Zinc supplementation from both sources linearly increased (P< 0.01) tibia Zn. Weight gain and feed intake increased quadratically (P< 0.05) with the increasing levels of Zn from Bioplex Zn® and increased linearly with the increasing levels of Zn from ZnSO4. 7H2O. Slope-ratio analysis regressing weight gain and tibia zinc content on supplemental Zn level below the inflection points indicated the relative bioavailability value of Bioplex Zn® compared with zinc sulfate were 183% and 157% for weight gain and tibia Zn content respectively. Broken-line analysis of the weight gain data determined the required supplemental level of Zn as Bioplex Zn® was 9.8 mg/kg of diet for optimal weight gain.